A mouse model of coronary microvacsular disease using a photochemical approach - Wang, Xinlu; Liu, Fang; Zhuang, Zhen W (Journal of Cardiology and Cardiovascular Medicine, 2019)
The development of reproducible rodent models of coronary microvascular disease (MVD) is essential for the early detection, treatment, and mechanism study of the pathophysiology. We hypothesized that endothelial dysfunction and subsequent microthrombi in the coronary arterioles, two early events in clinical coronary MVD, could be reproduced by photochemical reaction (PCR) technology in mice hearts. After rose bengal (one of photosensitizers) was administrated systemically, a green light was locally used to activate the photosensitizer, inducing over-production of oxidative stress in the heart. Following PCR, animals demonstrated reproducible endothelial injury, occlusion in arterioles, focal ischemia, and infarct-let with preserved cardiac function. Our technique has proven to be a reliable and reproducible means of creating coronary MVD in mice. We believe that this is an ideal model for developing a novel molecular tracer for earlier detection of coronary MVD, for testing new anti-fibrinolytic drugs, and for investigating the complex pathophysiology of coronary MVD. The protocol for establishing this model takes about thirty to forty minutes.